Local Void Fractions and Bubble Velocity in Vertical Air-Water Two-Phase Flows Measured by Needle-Contact Capacitance Probe - Shanfang Huang; Xiangxiang Wu; Benyang Zong; Yugao Ma; Xiaoyu Guo; Dong Wang (Science and Technology of Nuclear Installations)
Multiphase flow measurements have become increasingly important in a wide range of industrial fields. In the present study, a dual needle-contact capacitance probe was newly designed to measure local void fractions and bubble velocity in a vertical channel, which was verified by digital high-speed camera system. The theoretical analyses and experiments show that the needle-contact capacitance probe can reliably measure void fractions with the readings almost independent of temperature and salinity for the experimental conditions. In addition, the trigger-level method was chosen as the signal processing method for the void fraction measurement, with a minimum relative error of −4.59%. The bubble velocity was accurately measured within a relative error of 10%. Meanwhile, dynamic response of the dual needle-contact capacitance probe was analyzed in detail. The probe was then used to obtain raw signals for vertical pipe flow regimes, including plug flow, slug flow, churn flow, and bubbly flow. Further experiments indicate that the time series of the output signals vary as the different flow regimes and are consistent with each flow structure.